(untitled) (Al-Academy, 2023)
The research tagged (functional enhancement and its reflection on industrial product systems) focused on the possibility of enhancing industrial products in terms of form and functionality in a way that they are able to meet the needs of the user through the impact of technology and modern technologies on the functional enhancement of industrial products and their effectiveness in achieving formal and functional design variables, and producing products Industrial products are highly efficient and durable in order to improve them in order to meet the needs of the user, the transfer of technology between life forms and industrial products is desirable because the functional enhancement processes that occurred in general on industrial products by some designers developed human needs in a way that exceeded his expectations, which made The user lives in luxury in the use of products and shortens him a lot of time in the performance of daily tasks and the promotion of industrial products in proportion to the requirements of the contemporary user is necessary to meet the needs of the user, and the current research touched on a theoretical framework that includes three sections, we will address them successively.